HUMAN RESOURCES DEVELOPMENT IN NASHIK DISTRICT: A GEOGRAPHICAL ANALYSIS - Ahire, Dhanraj Kalu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present investigation studies the human resources development in the Nashik district through a geographical analysis. It is based on secondary data collected from socio-economic abstracts of the Nashik district (2021-22), District census handbook (2011) & District Gazetteers. This study took into account a wide range of human resources development indicators, including the total population, sex ratio, child sex ratio, percentage of tribal population, percentage of schedule cast population, literacy rate, female literacy rate, population density, percentage of the working population, primary health centers, numbers of sub-centers, numbers of doctors, numbers of nurses, per capita electricity consumption, and number of banks. The Min-Max Normalization Index technique is applied to analyze the human resources development of tribal communities. The human resources development in the study region reflected the regional diversity under analysis. Nashik and Malegoan exhibited high levels of human resources development. The tahsils of Niphad, Peint, Igatpuri, Dindori, Sinnar, Baglan, Triembak, Surgana, and Kalwan recorded moderate human resource development. Yeola, Chandwad, Deola, Nandgoan, Tahsil have recorded the lowest human resources development. Thus, the uneven human resource developments in the Nashik district affect physical features like topography and rainfall, as well as manmade features like population composition, medical facilities, literacy level, infrastructural facilities, urbanization, agriculture, and industrial growth. The present paper gives a geographical analysis of the human resources development in the Nashik district.